Vijfde van serie van 6 kerst- en nieuwjaarskaarten "naar platen uit de verzameling van den heer Van Stolk" (1917)
Vijfde van serie van 6 kerst- en nieuwjaarskaarten "naar platen uit de verzameling van den heer Van Stolk".